2005
DOI: 10.12723/mjs.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Oxidation of Benzoin by N. Bromosuccinimide

Abstract: Kinetics of Oxidation of Benzoin by N. Bromosuccinimide[NBS] 80% aqueous acetic acid has been investigated. The reaction follows first-order kinetics with respect to both[NBS] and [benzoin]. The effect of varying ionic strength and dielectric constant indicate the reaction is dipole-dipole type. Addition of succinimide(>NH), has a retarding effect on the rate of oxidation. The product of oxidation is benzil. By studying the effect of temparature on the reaction rate, the Arrhenius and the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Furthermore NBS has been extensively used for the oxidation of organic compounds, in this case the oxidation proceeded via the bromium ion (Br + ) in polar media, or through a free radical path involving homolytic dissociation of (NBS). , Kinetics of benzoin oxidation by [NBS] in 80% aqueous acetic acid has been investigated; the reaction followed first-order kinetics with respect to both [NBS] and [benzoin]. The effect of varying ionic strength and the dielectric constant indicated that the reaction is a dipole–dipole type . Moreover, the oxidation of 3-carboxy-3-hydroxy pentanedioic acid (citric acid) by (NBS) in an acetic acid/sodium acetate buffered medium (pH 3.6–5.2) was carried out at 308 K and constant ionic strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore NBS has been extensively used for the oxidation of organic compounds, in this case the oxidation proceeded via the bromium ion (Br + ) in polar media, or through a free radical path involving homolytic dissociation of (NBS). , Kinetics of benzoin oxidation by [NBS] in 80% aqueous acetic acid has been investigated; the reaction followed first-order kinetics with respect to both [NBS] and [benzoin]. The effect of varying ionic strength and the dielectric constant indicated that the reaction is a dipole–dipole type . Moreover, the oxidation of 3-carboxy-3-hydroxy pentanedioic acid (citric acid) by (NBS) in an acetic acid/sodium acetate buffered medium (pH 3.6–5.2) was carried out at 308 K and constant ionic strength.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of varying ionic strength and the dielectric constant indicated that the reaction is a dipoleÀdipole type. 14 Moreover, the oxidation of 3-carboxy-3-hydroxy pentanedioic acid (citric acid) by (NBS) in an acetic acid/sodium acetate buffered medium (pH 3.6À5.2) was carried out at 308 K and constant ionic strength. The reaction rate was described as first order with respect to both 3-carboxy-3-hydroxy pentanedioic acid and NBS.…”
Section: Introductionmentioning
confidence: 99%